Increase of sharpness for account of replacement of brightness intensity shade of image - Фалий, Вячеслав Виталиевич (Eastern-European Journal of Enterprise Technologies, 2012)
An approach of the construction of increase sharpness filters having regard to account the feature of digital image is ofered